AMMI Analysis for Green Pod Yield Stability of Snap Bean (Phaseolus vulgaris L.) Genotypes Evaluated in East Shewa Zone, Oromia, Ethiopia - Dinsa, Temesgen; Balcha, Urgaya; Tadesse, Fisseha (Journal of Scientific Agriculture, 2022)
The experiment was conducted at Adami Tulu Agricultural Research Center (ATARC), Lume and Dugda Districts during the 2019 and 2020 main cropping seasons to identify adaptable and high yielder snap bean genotypes for East Shewa Zone and similar agro ecologies. Ten snap bean genotypes were used as planting material. The experiment was laid down in Randomized Complete Block Design (RCBD) with three replications. The AMMI model shows that the environment accounted for 40.93%, GXE 31.79%, and genotype 12.70% of the total variation. The high percentage of the environment indicates that the major factor influencing the yield performance of snap beans is the environment. The first two IPCAs are the most accurate model that could predict the genotype’s stability and explained by IPCA-I (53.10%) and IPCA-II (21.1%) of GEI. This result revealed that there were differential yield performances among snap bean genotypes across testing environments due to the presence of GEI. According to stability parameters (ASV, and GGE Biplot) and mean yield results revealed that G-24 and G-12 genotypes are the most stable genotypes across test locations. Therefore, G-24 and G-12 were proposed as candidate genotypes for possible release.